Immunomodulatory actions of tonifying polysaccharides: pharmacological effects, mechanisms and therapeutic applications - Li, Jin-Yu; Yi, Chang; Zhu, Meng-Qin; Yuan, Yan-Feng; Chen, Guang; Qiu, Ning-Ning; Shen, Lei; Song, Li-Ya; Liu, Wen-Long; Zhang, Xi-Li (Frontiers in Immunology, 2025)
Tonifying polysaccharides, as a class of natural medicines, have attracted considerable interest due to their low toxicity, high safety profile, and excellent stability. Investigations have highlighted the significant impact of polysaccharides derived from Chinese medicinal herbs on the modulation of immune responses, significantly enhancing the functionality of immune organs such as the spleen, thymus, bone marrow, and intestines, stimulating immune cell proliferation and activation of T and B lymphocytes, macrophages, natural killer cells, and dendritic cells, and regulating the secretion and release of immune factors, thereby enhancing overall immune function. Tonifying polysaccharides, such as those found in medicinal herbs like ginseng and Astragalus, have demonstrated significant therapeutic effects in treating immune-mediated diseases, including anti-tumor, anti-autoimmune, and anti-viral activities. Despite the extensive literature published on the pharmacological effects, mechanisms, and therapeutic applications of Tonifying polysaccharides, there remains a lack of systematic organization and summarization. This review summarizes recent research findings on Tonifying polysaccharides within the field of immunomodulation. The research explores the immunomodulatory mechanisms and therapeutic applications of polysaccharides, clarifying their roles in enhancing immune function and their potential in clinical treatments, and aims to establish a robust theoretical framework and scientific foundation for the investigation and practical application of Tonifying polysaccharides, drawing on the extensive research on their structural complexity, biological activities, and clinical applications, thereby promoting their development and application as immune-enhancing agents in traditional Chinese medicine and as vaccine adjuvants